Returns to the education of the heads of home in the Region of Puno, 2011–2015 - Paredes Mamani, René Paz (2016)
The aim of the study was econometrically measure the returns to education of heads of households in the region of Puno, based on the National Household Survey 2011–2015. The results using Mincer theory and methodology Heckman, show that there are positive and signiﬁcant returns attributed to the education of household heads, ie, a higher level of education there is greater economic compensation per hour worked. For each additional year of education, an additional increase of 12.36% in salary would be generated. According to the levels of educational attainment, household heads with no education would get a return of S/. 1.20 per hour with primary education S/. 2.24 per hour with secondary education S/. 3.36 per hour, non-university higher education S/. 5.54 hour with university education S/. 8.24 per hour and graduate S/. 10.92 per hour.